PREGNANCY GINGIVITIS SEBAGAI FAKTOR RISIKO KEKURANGAN ENERGI KRONIS (KEK) IBU HAMIL DI PUSKESMAS TRIMULYO, PESAWARAN - Antun Rahmadi; Ratnasari Dyah Purnomowati (Universitas Pahlawan, 2022)
Chronic Energy Deficiency (CED) is a nutritional problem that often occurs in pregnant women. Pevalence in Indonesia is 17.3%, in Lampung Province it is 13.62%, and in Pesawaran Regency it is 20.6%. The highest CED in Pesawaran Regency were in Trimulyo Health Center. The purpose of this study was to obtain an overview of the incidence of CED and gingivitis and to analyze the relationship between the two variables. Cross sectional study with a population of 56 pregnant women who were determined purposively. Data collection methods are interviews, examination and measurement To obtain gingivitis data, gum and mouth examinations were carried out, while CED measured by MUAC. The bivariate analysis was carried out with the chi square test to see the relationship between gingivitis and CED. The incidence of CED in pregnant women at the Trimulyo Health Center was 21.4% and gingivitis was 48.2%. The results of statistical test (p value 0.006) which means there is a significant relationship between gingivitis and CED . The odds ratio of 95% CI is 7.9 (1.5-40.7). CED and the incidence of gingivitis in pregnant women at the Trimulyo Health Center is a public health problem. Pregnancy gingivitis is a risk factor for CED in pregnant women at the Trimulyo Health Center, Pesawaran. Pregnant women who has gingivitis are at risk of 7.9 times become CED compared to normal pregnant women..